IMPACT OF MAIN TILLAGE AND FERTILIZER SYSTEMS ON THE YIELD OF CORN GRAIN AND ITS QUALITY - Олепір, Роман; Ласло, Оксана; Воропін, Микола; Барило, Антон (SWorldJournal, 2025)
Corn is one of the most productive cereal crops of universal purpose, which is distinguished by high yield, a wide range of uses and the ability to adapt to various soil and climatic conditions. The main task in solving the issue of increasing the level o